Training socially accountable clinician-citizens: integrating clinical public health education in a medical school curriculum - Kofi Essel; Hana Akselrod; Sonal Batra; Candice Dawes; Zareen Zaidi; Lawrence Deyton (Medical Education Online)
By adopting a holistic perspective that looks ‘upstream’ at the underlying determinants of health, physicians can develop more effective strategies for promoting wellness and reducing health inequities in an increasingly diverse and complex society. Public health focuses on disease prevention and promotion of health through organized efforts by individuals and society. Population health focuses on the health outcomes of a group of individuals. We designed the Clinical Public Health curriculum, a pedagogical framework designed at the George Washington University School of Medicine & Health Sciences that breaks down traditional silos between didactic public and population health teaching, patient care and community engagement for medical students. It aims to train socially accountable clinician-citizens through an integrated, longitudinal curriculum across the four years of medical school. In this article we describe one aspect of the curriculum – four self-contained ‘summits’ – which can be used as a template for others seeking to develop a curriculum focusing on social accountability and engagement with community and governmental partners. During these multi-day applied educational experiences, medical students engage with key stakeholders, community members, community-based organizations, and state and national agencies to develop innovative approaches to engage in advocacy and population health. Enhanced medical school curricula focusing on the development of socially accountable clinician-citizens is an urgent need to develop more meaningful clinical-community interventions, support professional development, put context on the impact of health-related social needs on patients and families, and transform healthcare delivery and policy through greater community connection and advocacy.